La servante dans le monde romain : une figure oubliée - Sophie Mano (Pallas, 2013)
Studies mentioning women’s activities in the Roman world do exist, they are actually numerous and detailed. Yet they only refer to various specialities even when they solely deal with the domestic staff. The simple maid servant, a slave “without qualification” and “without specialization” is however very present in the various kinds of sources (juridical, epigraphic, literary texts) ; she nevertheless remains a neglected figure. True, the ancillae, ministrae, pedisequae, seem to have belonged to the lowest, most insignificant servile labour force. Now the small credit accorded to the personage, to her designation and functions, is unjustified. The absence of speciality does not entail inexistence and the collected data can draw out the ancilla and her sister slaves from the relative silence to which they are confined. Being in turns “uterus”, optima ancilla, scapegoat, confident, mistress, substitute or lady’s maid, she finally at the end of our analysis presents herself as a central figure essential to the functioning of the domestic staff but also to the imaginary world of the Romans.